Equity Crowdfunders' Human Capital and Signal Set Formation: Evidence From Eye Tracking. (September 2022) - Butticè, Vincenzo; Collewaert, Veroniek; Stroe, Silvia; Vanacker, Tom; Vismara, Silvio; Walthoff-Borm, Xavier
Signaling theory typically assumes that attention is always given to observable signals. We study signal receivers' formation of signal sets—the signals to which receivers attend and that they can use for subsequent interpretations. Drawing on a cognitive perspective, we argue that signal receivers' human capital influences the volume and type of signals they attend to and the time they take to form signal sets. Using eye tracking, we show that equity crowdfunders do not attend to many signals that are easily observable on a campaign page, and that differences in crowdfunders' human capital uniquely affect their signal set formation.